2018
DOI: 10.1634/theoncologist.2018-0464
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Pazopanib in Patients with Metastatic Alveolar Soft Part Sarcoma

Abstract: Lessons Learned. Pazopanib shows a modest efficacy in metastatic alveolar soft part sarcoma.Clinical outcomes were comparable to those in previous studies using antiangiogenic drugs.Further prospective studies evaluating the benefit of pazopanib in alveolar soft part sarcoma with a larger sample are warranted to validate results.Background.Alveolar soft part sarcoma (ASPS) is a rare mesenchymal malignant tumor characterized by an unbalanced translocation, t(X;17)(p11.2;q25), which leads to the fusion of ASPSCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…After the initiation of this study, some prospective and retrospective reports on the effectiveness of pazopanib in ASPS were published. Kim et al reported a phase II trial of pazopanib in patients with metastatic ASPS 27 . Six patients were enrolled in the study, with 1 patient achieving PR, and 5 patients showing SD according to RECIST (response rate 16.7%).…”
Section: Discussionmentioning
confidence: 99%
“…After the initiation of this study, some prospective and retrospective reports on the effectiveness of pazopanib in ASPS were published. Kim et al reported a phase II trial of pazopanib in patients with metastatic ASPS 27 . Six patients were enrolled in the study, with 1 patient achieving PR, and 5 patients showing SD according to RECIST (response rate 16.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Pazopanib, the phase 3 trial of which was discussed above in Section 3, is a TKI that inhibits VEGF receptors as well as other growth factors, and there are retrospective clinical reports that suggested pazopanib treatment resulted in relatively higher response rates in vascular-abundant VEGF-expressing sarcomas compared to other histological subtypes [48]. Patients with an alveolar soft part sarcoma (ASPS), characterized by translocation t(X;17)(p11.2;q25) and known as a vascular-rich tumor, showed high responses to VEGF-targeted therapies in prospective trials, including trials of pazopanib [49][50][51].…”
Section: Investigating Molecular Targeted Therapies For Sts Patientsmentioning
confidence: 99%
“…[10] However, disease progression commonly developed with VEGFR-TKI treatment and demonstrated a median progression-free survival (PFS) of [13][14][15][16][17][18][19] months with sunitinib, 5.5-13.6 months with pazopanib and 10.1 months with cediranib. [7,[9][10][11][12][13] Immune checkpoint inhibitors (ICIs) represented encouraging effects in ASPS patients. [14][15][16] Groisberg R et al reported two of four patients, diagnosed with ASPS and enrolled in immunotherapy trials, who achieved a partial response (PR) lasting 8 and 12 months after previous 2-4 lines of treatment failure.…”
Section: Introductionmentioning
confidence: 99%